2017
DOI: 10.5853/jos.2016.01522
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Based Thrombus Imaging for the Prediction of Recanalization after Reperfusion Therapy in Stroke

Abstract: The prediction of successful recanalization following thrombolytic or endovascular treatment may be helpful to determine the strategy of recanalization treatment in acute stroke. Thrombus can be detected using noncontrast computed tomography (CT) as a hyperdense artery sign or blooming artifact on a T2*-weighted gradient-recalled image. The detection of thrombus using CT depends on slice thickness. Thrombus burden can be determined in terms of the length, volume, and clot burden score. The thrombus size can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 57 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…Previous studies have shown inconsistent findings in terms of the association between the thrombus burden and recanalization after mechanical thrombectomy by means of an SR 6 , 9 15 . The inconsistency between the studies might be partly ascribed to differences in the method used to measure thrombus burden and the number of patients 16 . Thrombus length and clot burden score could be surrogates for clot burden.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown inconsistent findings in terms of the association between the thrombus burden and recanalization after mechanical thrombectomy by means of an SR 6 , 9 15 . The inconsistency between the studies might be partly ascribed to differences in the method used to measure thrombus burden and the number of patients 16 . Thrombus length and clot burden score could be surrogates for clot burden.…”
Section: Discussionmentioning
confidence: 99%
“…Distal thrombus ends were evaluated either directly on susceptibility-weighted imaging, postcontrast T1, or thin-slice noncontrast CT or indirectly as indicated by the flowstagnation of collateralized vessels on late phase contrast-enhanced MRA or late phase CTA. 16 Thrombus length was calculated using a freehand curve function as measurements between the proximal and distal thrombus ends.…”
Section: Preinterventional Diagnostic Work Upmentioning
confidence: 99%
“…These numbers increased to 13 (95% CI, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and 35 (95% CI, 18-464) when analysis was confined to M1 (proximal and distal) and ICA occlusions (SWIFT DIRECT trial cohort [Solitaire With the Intention for Thrombectomy Plus Intravenous t-PA Versus DIRECT Solitaire Stent-Retriever Thrombectomy in Acute Anterior Circulation Stroke], URL: http://www.clinicaltrials. gov.…”
Section: Number Needed To Treatmentioning
confidence: 99%
“…Although our analyses and experiments were carried out in two dimensional space, the case in three dimension is similar. In general, acquiring a vascular shape in the human body is feasible by means of some techniques, including magnetic resonance imaging [28,29], computed tomography [30], and angiography [31]. In a three dimensional environment, the guidance of magnetotactic bacterial microrobots could also be achieved if three dimensional channels are content with the similar monotonic functions (i.e.…”
Section: Discussionmentioning
confidence: 99%